Durability of CFRP sheets and epoxy resin exposed to natural hygrothermal or cyclic wet‐dry environment. Issue 2 (11th December 2017) - Xie, Jianhe; Lu, Zhongyu; Guo, Yongchang; Huang, Yaohong
Abstract : Fiber reinforced polymer (FRP) composites are used in harsh environments, resulting in degradation of their mechanical properties. Such degradation is critical in terms of the reliable design and application of FRP composites. In this study, a set of CFRP flat coupons and epoxy resin matrix flat coupons were prepared and subjected to alternating conditions of 10 h immersion in a 40°C NaCl solution with a concentration of 3.5%, and 14 h drying at 25°C and 60% relative humidity (RH). They were divided into five series, subjected to 0, 60, 120, 240, and 360 wet‐dry cycles, respectively. For a comparison with the acceleration simulation tests, the same numbers of specimens were exposed to a natural hygrothermal environment for 0, 6, 12, 18, and 30 months, respectively. After removal from the environment at the designated time, a series of tension tests were carried out. Based on the experimental results, the relationship regarding the tensile strength degradation of the CFRP sheets between the natural hygrothermal environment and the cyclic wet‐dry environment was determined. It was found that the tensile modulus of the CFRP sheets increased by 1.4%, and the tensile strength and ultimate strain decreased by 8.1% and 8.0% after 360 wet‐dry cycles, respectively. After a 30‐month natural exposure period, the tensile strength, tensile modulus, and ultimate strain of the CFRP sheets decreased by 9.9%, 3.4%, and 7.2%, respectively. The tensile property of the epoxy resin matrix appeared to be more sensitive to these two types of exposure environments than that of the CFRP sheets, and the tensile strength decreased by 59.4% at the end of 30‐month exposure. POLYM. COMPOS., 40:553–567, 2019. © 2017 Society of Plastics Engineers